A clinico-pathological study of posterior triangle neck swelling: a case series - Tonape, Trupti; P. Lad, Aditya; Shetty, Iresh; Raval, Bhoomi; Kumar Balasubramanian, Sree (International Surgery Journal, 2017)
Background: The neck swelling is often surrounded by mystique in arriving at a diagnosis as well as in its management. There are many good approaches to a patient with a swelling in the neck. Methods: This study was done in Dr. D. Y. Patil Medical College Hospital and Research Centre, Pune. In this study, we have taken 30 cases in study group. Only posterior triangle neck swellings were considered during the study. Clinico-pathological co-relation was done during the study. Results: In the present study group of 30 patients we found 10 patients to be having Lymphadenitis which includes both tuberculous and non-tuberculous, 8 patients to be having lipoma, 4 patients to be having neck secondaries, 2 patients of cystic hygroma and 6 nonspecific causes like cavernous haemangioma, madelung disease, Kikuchi Fujimoto disease. Further histological co-relation was done. Conclusions: Incidence of different types of neck swellings were found and rare diseases like Madelung’s disease and Kikuchi fujimoto’s disease.